Perceived Stress During the COVID-19-Related Confinement in Cyprus - Kyprianidou, Maria; Christophi, Costas A.; Giannakou, Konstantinos (Frontiers in Public Health, 2021)
The COVID-19 pandemic is a serious global health emergency that could potentially have a significant impact on both somatic as well as psychological level. The aim of this study was to assess the prevalence of perceived stress in the general adult population of Cyprus during the first COVID-19 lockdown period. This was an internet-based cross-sectional study conducted between 6 April and 20 June 2020, one to two and a half months after the introduction of and the first mandatory lockdown on its entire territory imposed by the government of the Republic of Cyprus on 24 March 2020. Data collection was done using a self-administered questionnaire that included information about socioeconomic and demographic characteristics, physical activity, smoking habits, and stress level. A total of 1,485 adults participated in the study. The median perceived stress score was 10 (q1 = 6, q3 = 15). Linear regression models showed that having a medium monthly income (€501-1,500) and being a current smoker was positively associated with the perceived stress score, while being male and physically active was negatively associated with the perceived stress score (all p <0.05). People with medium average salary and current smokers were at a higher risk for perceived stress. Psychological interventions and/or psychological services provided in certain vulnerable groups would be beneficial in future lockdowns due to either COVID-19 or a new pandemic.